Iowa RBA, January 4, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for January 4, 1998. Highlights include Spotted Towhee, Thayer's Gull and Long-tailed Duck. Includes updates for January 6, 1998 and January 7, 1998. Epson - sheet feed/flatbed